PENGARUH SPONSOR OLAHRAGA TERHADAP MINAT MEMBELI KACANG DUA KELINCI :SURVEI PADA ANGGOTA FORUM MADRIDISTA INDONESIA REGIONAL KOTA BANDUNG - Mika Maulana, - (2011)
The global economic crisis has accelerated the shift of world economic power. Economic recovery in Asia provide a positive sentiment for Indonesia's economic growth is faster. Manufacturing sector contributed greatly to economic growth in Indonesia. This causes the food and beverage processing industries have a competitive rivalry especially peanut industry is currently experiencing due to the rapid progress that many manufacturers there are nuts on the Indonesians and the number of brands sold peanuts. Dua Kelinci as the leading peanut producer in Indonesia have a problem on a low market share gains. Therefore, in order to remain competitive Dua Kelinci do sport sponsorship strategy in order to attract the attention of consumers so as to increase the purchase intention. This study was conducted to analyze the effect of sport sponsorship on purchase intention. Sport sponsorship is an independent variable (X) consists of dimensions sponsor receptiveness and sponsor integrity. While the dependent variable is purchase intention (Y) then that becomes the dependent variable (dependent variable) purchase intention of positive attitude towards the brand and brand familiarity. The type of research which applied is descriptive verificative, and the method which applied is explanatory survey with simple random sampling technique with number of samples are 100 respondents. The research was carried out within less than one year, then the research method used is the method of cross-sectional method (cross-approach) and data analysis techniques using simple linear regression with the auxiliary is computer software SPSS 16.0. The results stated that the sports sponsorship have influence for 61.93% on the purchase intention. From the results of hypothesis testing can be seen that sport sponsorship has a positive influence on purchase intention. Keywords: sport sponsorship, purchase intention.